Enzyme-labelled immunosorbent assay techniques in foot-and-mouth disease virus research. - Abu Elzein, E. M. (Cambridge University Press, 1978)
The indirect ELISA technique has been developed successfully to measure antibodies to foot-and-mouth disease virus (FMDV) in cattle sera. Preliminary studies using a standard serum assay show that reproducible results are obtained. The method should prove useful for the examination of antibody titres in sera from large numbers of cattle or other animals.